1990
DOI: 10.1159/000186118
|View full text |Cite
|
Sign up to set email alerts
|

Beta-2-Microglobulin Generation Rate and Clearance Rate in Maintenance Hemodialysis Patients

Abstract: We analyzed the rebound pattern of plasma β2-microglobulin (β2-m) concentration from 4 h after completion of hemodiafiltration until the start of the next treatment according to the one-pool β2-m kinetic model so as to determine β2-m generation rate and whole-body β2-m clearance. Next, we obtained the whole renal β2-m clearance as the product of renal creatinine clearance and the glomerular sieving coefficient of β2-m. Then, extrarena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…22,23 HD patients with RRF are also known to have lower levels of b2-microglobulin, better nutritional status and better quality of life. [24][25][26][27] Consistent with these studies, compared with our thrice-weekly HD group, our twice-weekly HD group had a significantly lower level of serum b2-microglobulin at the end of the follow-up period. We believe this may be attributable to the higher RRF in the twice-weekly group.…”
Section: Discussionsupporting
confidence: 76%
“…22,23 HD patients with RRF are also known to have lower levels of b2-microglobulin, better nutritional status and better quality of life. [24][25][26][27] Consistent with these studies, compared with our thrice-weekly HD group, our twice-weekly HD group had a significantly lower level of serum b2-microglobulin at the end of the follow-up period. We believe this may be attributable to the higher RRF in the twice-weekly group.…”
Section: Discussionsupporting
confidence: 76%
“…The serum concentration of ß 2 -microglobulin is accounted for by its generation rate, duration of dialysis treatment, and whole body clearance (renal plus extrarenal clearance) [20]. In our study, these results suggest that the improved clearance of ß 2 -microglobulin could not completely account for the lower predialysis ß 2 -microglobulin observed in HDF-treated patients.…”
Section: Discussionmentioning
confidence: 53%
“…The use of a highly biocompatible membrane-like polysulfone, and an ultrapure/sterile dialysate, have been reported to be associated with lower ß 2 -microglobulin serum concentrations [21], a reduced incidence of carpal tunnel syndrome [22], and a decreased degree of inflammatory cytokine induction [23]. Maeda et al [20] reported that ß 2 -microglobulin generation is not stimulated by the polysulfone membrane during HDF. Thus, the combination of a significant removal of ß 2 -microglobulin and other middle to large molecular uremic toxins, with a lower inflammatory stimulation through using a biocompatible membrane and a sterile fluid system, may all play a role in the observed lower predialysis ß 2 -microglobulin level in our HDF patients.…”
Section: Discussionmentioning
confidence: 99%
“…In HDF there is even less data. Maeda et al [22] studied the rebound in plasma ␤ 2 M levels following HDF and concluded that their variation within individual patients was solely attributable to the variation in residual renal function. The half-life of 131 I-␤ 2 M was less in haemofiltered than in haemodialysed patients, but similar to that in patients with residual renal function [23] .…”
Section: Discussionmentioning
confidence: 99%